C-Reactive Protein-Albumin Ratio (CAR): A More Promising Inflammation-Based Prognostic Marker for Patients Undergoing Curative Hepatectomy for Hepatocellular Carcinoma - Mai RY; Lu TL; Lu RJ; Zeng C; Lian F; Li LQ; Wu GB; Ye JZ (Dove Medical Press, 2024)
Rong-Yun Mai,1,* Ting-Li Lu,1,* Ri-Jin Lu,1 Can Zeng,1 Fang Lian,2 Le-Qun Li,1 Guo-Bin Wu,1 Jia-Zhou Ye1 1Department of Hepatobiliary & Pancreatic Surgery, Guangxi Medical University Cancer Hospital, Nanning, 530021, People's Republic of China; 2Department of Physiology, Basic Medical College, Guangxi Medical University, Nanning, 530021, People's Republic of China*These authors contributed equally to this workCorrespondence: Jia-Zhou Ye; Guo-Bin Wu, Department of Hepatobiliary & Pancreatic Surgery, Guangxi Medical University Cancer Hospital, 71 He Di Road, Nanning, 530021, People's Republic of China, Tel +86-771-5310045, Fax +86-771-5312000, Email yejiazhou@gxmu.edu.cn; wuguobin@gxmu.edu.cnBackground: Systemic inflammatory response is a hallmark of cancer and plays a significant role in the development and progression of various malignant tumors. This research aimed to estimate the prognostic function of the C-reactive protein-albumin ratio (CAR) in patients undergoing hepatectomy for hepatocellular carcinoma (HCC) and compare it with other inflammation-based prognostic scores, including the neutrophil-lymphocyte ratio, platelet-lymphocyte ratio, monocyte-lymphocyte ratio, systemic immune inflammation index, prognostic index, Glasgow prognostic score, and modified Glasgow prognostic score.Methods: Retrospective analysis was conducted on data from 1039 HCC cases who underwent curative liver resection. The prognostic performance of CAR was compared with other scores using the area under the time-dependent receiver operating characteristic (t-ROC) curve. Multivariable Cox regression analyses were performed to confirm independent predictors for disease-free survival (DFS) and overall survival (OS).Results: The area under the t-ROC curve for CAR in the evaluation of DFS and OS was significantly greater than that of other scores and alpha-fetoprotein (AFP). Patients were stratified based on the optimal cut-off value of CAR, and the data revealed that both DFS and OS were remarkably worse in the high-CAR set compared to the low-CAR set. Multivariable Cox analysis demonstrated that CAR was an independent prognostic parameters for assessing DFS and OS. Regardless of AFP levels, all patients were subsequently divided into significantly different subgroups of DFS and OS based on CAR risk stratification. Similar results were observed when applying CAR risk stratification to other scoring systems. CAR also showed good clinical applicability in patients with different clinical features.Conclusion: CAR is a more effective inflammation-based prognostic marker than other scores and AFP in predicting DFS as well as OS among patients with HCC after curative hepatectomy.Keywords: hepatocellular carcinoma, hepatectomy, systemic inflammation response, inflammation-based prognostic marker, C-reactive protein to albumin ratio